High Performance Mg2(Si, Sn) Solid Solutions: a Point Defect Chemistry Approach to Enhancing Thermoelectric Properties. (1st April 2014) - Jiang, Guangyu; He, Jian; Zhu, Tiejun; Fu, Chenguang; Liu, Xiaohua; Hu, Lipeng; Zhao, Xinbing
<x xml:space="preserve">Abstract</x> A point defect chemistry approach to improving thermoelectric (TE) properties is introduced, and its effectiveness in the emerging mid‐temperature TE material Mg2(Si, Sn) is demonstrated. The TE properties of Mg2(Si, Sn) are enhanced via the synergistical implementation of three types of point defects, that is, Sb dopants, Mg vacancies, and Mg interstitials in Mg2Si0.4Sn0.6‐xSbx with high Sb content (x > 0.1), and it is found that i) Sb doping at low ratios tunes the carrier concentration while it facilitates the formation of Mg vacancies at high doping ratios (x > 0.1). Mg vacancies act as acceptors and phonon scatters; ii) the concentration of Mg vacancies is effectively controlled by the Sb doping ratio; iii) excess Mg facilitates the formation of Mg interstitials that also tunes the carrier concentration; vi) at the optimal Sb‐doping ratio near x ≈ 0.10 the lattice thermal conductivity is significantly reduced, and a state‐of‐the‐art figure of merit ZT > 1.1 is attained at 750 K in 2 at% Zn doped Mg2Si0.4Sn0.5Sb0.1 specimen. These results demonstrate the significance of point defects in thermoelectrics, and the promise of point defect chemistry as a new approach in optimizing TE properties.